META-ANALISIS PENGARUH ALQURUN TEACHING MODEL TERHADAP KEMAMPUAN MATEMATIS - Sugeng Sutiarso (STKIP Andi Matappa, 2020)
Alqurun Teaching Model (ATM) is a new learning model that has been implemented in several schools (junior and senior high schools). To ensure that ATM has an influence on mathematical ability, a meta-analysis was carried out by calculating the effect size. This descriptive study aims to analyze the effect size of ATM on students' mathematical abilities. The research subjects were 16 research students mathematics education at Faculty Teacher and Training Education, Lampung University. The research data were obtained through observation of 979 students. Data were analyzed descriptively through 3 simultaneous stages, namely (1) identification/coding of data, (2) calculating effect sizes, and (3) interpreting effect sizes according to certain criteria. The results of data analysis show that (1) the overall effect size of ATM on students' mathematical abilities is 1.00 (high) when compared to the problem based learning model of 0.63 (moderate), discovery learning model of 0.76 (moderate), and a project based learning model of 0.63 (moderate), (2) categorically: (i) ATM is predicted to be better implemented at the SMA level than SMP, (ii) ATM is predicted to be better at using LKPD media than teaching materials and PPT media, and (iii) ATM is predicted to provide higher learning outcomes in understanding concepts than communication, representation, and mathematical problem solving. Based on the results of this analysis, it is concluded that ATM can be used as an alternative to the mathematics learning model in the 2013 curriculum